Food and housing security at a US Hispanic-Serving Institution: An examination before and during the COVID-19 pandemic - Wagler, Amy; Schober, Gregory S.; Chavez-Baray, Silvia M.; Ayala, Jessica; Dessauer, Paul R.; Moya, Eva M. (Frontiers in Public Health, 2022)
University students occupy a socially marginal position and therefore are often underserved by academic and service institutions. This article presents how The University of Texas at El Paso, a premier Hispanic-Serving Institution located in the U.S.-Mexico Border region, with predominantly first-generation students from underserved areas, addresses food insecurity and housing insecurity using a student success model consisting of a campus pantry, social services, and educational and psychological counseling. Findings of a sample of n=7633 university students are presented in the first cross-sectional exploratory two-year food and housing security study on campus administered via platform Campus Labs Baseline in academic year 2019-2020 and 2020-2021. The first sample consisted of n=2615 students representing 10.4% of enrollment (25,177 total 2019 enrollment) and the second sample in 2020-2021 was n=5018 representing 20.2% of student enrollment (24,879 total 2020 students). To measure food insecurity, the six-item short form of the U.S. Department of Agriculture (USDA) Household Food Security Survey Module was used. To document housing insecurity we created questions informed by student input. In this study, survey results are reported, and tests are conducted to assess impact of various student characteristics on the USDA defined levels of food insecurity. Student characteristics significantly impacting food insecurity are probed further using data visualizations and subpopulation analysis with a focus on analyzing factors impacted by the COVID-19 pandemic. Results indicate that employment status, consistent employment status, hours per week, academic level, number of dependents, and pronouns used are all factors associated with food insecurity during the pandemic but not prior to the pandemic. Other factors, including, college affiliation, ethnicity/race, having any dependents and being head of household, living alone, mode of campus transportation and mode of the transportation, household income, and age, all were associated with higher rates of food insecurity in both academic years. Using these results, a critical analysis of past interventions addressing food and housing insecurity is presented with a focus on changes made during the pandemic. Recommendations are made for further data-driven interventions and future steps.